Susceptibility of Candida albicans and Candida dubliniensis to erythrosine- and LED-mediated photodynamic therapy - Borges Pereira Costa, Anna Carolina [UNESP]; de Campos Rasteiro, Vanessa Maria [UNESP]; Pereira, Cristiane Aparecida [UNESP]; Hashimoto, Emily Setsuko Halter da Silva [UNESP]; Beltrame Junior, Milton; Junqueira, Juliana Campos [UNESP]; Cardoso Jorge, Antonio Olauo [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
The effect of erythrosine- and LED-mediated photodynamic therapy (PDT) on planktonic cultures and biofilms of Candida albicans and Candida dubliniensis was evaluated. Planktonic cultures of standardized suspensions (10(6) cells/mL) of C. albicans and C. dubliniensis were treated with erythrosine concentrations of 0.39-200 mu M and LEDs in a 96-well microtiter plate. Biofilms formed by C. albicans and C. dubliniensis in the bottom of a 96-well microtiter plate were treated with 400 mu M erythrosine and LEDs. After PDT, the biofilms were analysed by scanning electron microscopy (SEM). The antimicrobial effect of PDT against planktonic cultures and biofilms was verified by counting colony-forming units (CFU/mL), and the data were submitted to analysis of variance and the Tukey test (P < 0.05). C. albicans and C. dubliniensis were not detectable after PDT of planktonic cultures with erythrosine concentrations of 3.12 mu M or higher. The CFU/mL values obtained from biofilms were reduced 0.74 log(10) for C. albicans and 0.21 log(10) for C. dubliniensis. SEM revealed a decrease in the quantity of yeasts and hyphae in the biofilm after PDT. In conclusion, C. albicans and C. dubliniensis were susceptible to erythrosine- and LED-mediated PDT, but the biofilms of both Candida species were more resistant than their planktonic counterparts. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Candida albicans; Candida dubliniensis; Photodynamic therapy; Erythrosine; Light-emitting diode